2001
DOI: 10.1038/sj.onc.1204843
|View full text |Cite
|
Sign up to set email alerts
|

A mutated cathepsin-D devoid of its catalytic activity stimulates the growth of cancer cells

Abstract: Cathepsin-D, a lysosomal aspartyl proteinase, is highly secreted by breast cancer cells and its over-expression by transfection stimulates cancer cell proliferation. The mechanism by which this protease a ects proliferation remains, however, unknown. In order to determine whether proteolytic activity is necessary, we abolished its enzymatic activity using site-directed mutagenesis followed by stable transfection in 3Y1-Ad12 cancer cells. Substitution of the aspartic acid residue 231 by an asparagine residue in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
99
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(105 citation statements)
references
References 36 publications
5
99
0
1
Order By: Relevance
“…Previous studies in two cellular models, MCF-7 cells and rat embryo tumor cells, indicated that this mitogenic activity could be due to cath-D action as a protein ligand interacting with a mitogenic receptor (Fusek and Vetvicka, 1994;Glondu et al, 2001; reviewed by Rochefort and Liaudet-Coopman, 1999), or to the proteolytic activity of the enzyme. In rat tumor cells transfected with human cath-D cDNA, two distinct cath-D mitogenic activities were observed as a function of the cell density (Garcia et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in two cellular models, MCF-7 cells and rat embryo tumor cells, indicated that this mitogenic activity could be due to cath-D action as a protein ligand interacting with a mitogenic receptor (Fusek and Vetvicka, 1994;Glondu et al, 2001; reviewed by Rochefort and Liaudet-Coopman, 1999), or to the proteolytic activity of the enzyme. In rat tumor cells transfected with human cath-D cDNA, two distinct cath-D mitogenic activities were observed as a function of the cell density (Garcia et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The direct role of cath-D in cancer metastasis was first demonstrated in rat tumor cells in which transfectioninduced cath-D over-expression increased their metastatic potential in vivo (Garcia et al, 1990;Liaudet et al, 1994). In this rat tumor model, the cath-D mechanism responsible for metastasis stimulation seemed to have a positive effect on cell proliferation, favoring the growth of micro-metastases, rather than increasing the invasive potential (Garcia et al, 1990;Liaudet et al, 1994Liaudet et al, , 1995Glondu et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…We checked these results by investigating the effect of recombinant proteolytically inactive D231N pro-cath-D on the production of endogenous LRP1b-CTF in HMF .1(-) plasmids using Lipofectamine (Gibco-BRL, Life Technologies SAS, Villebon sur Yvette, France). pcDNA3.1(-)cath-D expression plasmid encoding human pre-pro-cath-D has previously been described (Vignon et al, 1986;Glondu et al, 2001Glondu et al, , 2002Berchem et al, 2002;Laurent-Matha et al, 2005;Hu et al, 2008). fibroblasts ( Figure 3C, panel a).…”
Section: Ectopic Cath-d and Pro-cath-d Inhibit Lrp1 Rip In Cos Cells mentioning
confidence: 99%
“…Cath-D affects both the cancer cells and the stromal cells of the tumor microenvironment. Human pre-pro-cath-D cDNA transfected in cancer cells promotes cancer cell proliferation, tumor angiogenesis, and tumor growth and metastasis (Glondu et al, 2001;Berchem et al, 2002). Human pre-pro-cath-D cDNA transfected in cath-DÀ/À MEF (mouse embryonic fibroblast) cells induces fibroblast outgrowth (LaurentMatha et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation